Effect of Victim Gender on Evaluations of Sexual Crime Victims and Perpetrators: Evidence from Japan - Tomoya Mukai (Sexes)
Recent legal reforms incorporating the concept of sexual consent into the Penal Code, alongside high-profile scandals involving male idol groups and comedians, have heightened societal attention to sexual crimes in Japan. Although studies have extensively examined this topic, findings have been predominantly from Western or English-speaking countries, which raises questions regarding their applicability to other cultural contexts. To address this gap, this study examined whether the results of prior research could be generalized to Japan. This study examined six hypotheses derived from previous studies. Using a vignette-based online survey (N = 748), participants read a hypothetical sexual assault case and answered questions on sentencing, negative social reactions, and victim/perpetrator blaming. An analysis revealed that only one hypothesis was supported: respondents recommended longer sentences for perpetrators when the victim was male rather than female. Additionally, women were more likely to exhibit egocentric reactions, such as expressing more anger toward the perpetrators than the victims, than men. No other hypothesized gender-based differences, which included victim-blaming or harsher sentencing by male observers, were supported. These findings highlight the risks of generalizing research findings across cultural contexts and emphasize the importance of conducting culturally specific studies.